Organizational health and independent sector healthcare organizations. (3rd July 2022) - Williams, Stephen P.; Purkayastha, Sanjay; Chaturvedi, Sankalp; Darzi, Ara
ABSTRACT: With an increasing proportion of UK healthcare delivered by independent sector providers (ISPs) it is important that performance data is reviewed with a similar rigour as within the public sector. However, there is a relative paucity of work considering quotients of performance in the independent healthcare sector. This study sets out to measure organizational health within ISPs in the UK and juxtapose this with contemporaneous data taken from public sector NHS organizations. Survey data was tested for construct validity with fit of the existing factor structure of the Healthcare-OH survey examined using confirmatory factor analysis (CFA). Multiple-group CFA was used to establish measurement invariance to permit comparison of latent sum scores between ISP and NHS organizations. Measurement invariance analysis evaluated the fit of sequential invariance models, proceeding iteratively to establish partial metric and scalar invariance. Latent sum scores comparisons demonstrated ISPs outperformed NHS trusts across all elements of organizational health. This is the first time organizational health has been measured in ISPs explicitly for comparison with results in the public sector. Comparative measurement and analysis in this way is novel and has the potential of fostering a two-way learning process for the ultimate benefit of both NHS and ISP organizations.